A policy framework for city eligibility analysis: TISM and fuzzy MICMAC-weighted approach to select a city for smart city transformation in India. (March 2019) - Kumar, Harish; Singh, Manoj Kumar; Gupta, M.P.
Highlights: City eligibility analysis is essential before selecting a city for smart cities mission. A coherent model has been proposed to analyze the city selection eligibility. The weights for factors have been calculated based on concept of driving power. Obtained weights can be utilized to select Top 'N' city for smart city transformation. Abstract: The increasing rate of urban population and deteriorating conditions of physical, institutional, social, and economic infrastructure in cities are demanding smarter ways to improve public utilities and services in India. Smart city development promotes an established, interconnected, and sustainable urban system. The Indian government has launched "100 Smart Cities Mission" for planned urbanization in the country. The "100 cities" have been selected from a two-round city challenge competition. However, some controversial viewpoints have made questionable remarks over the selection process. For the effective planning of smart cities, an exhaustive analysis is essential to find the existing critical infrastructure, key resources, and development trends. The purpose of this study is to aid city planners and decision-makers to determine city eligibility in a multidimensional way and to develop evaluation criteria for city selection process to meet the goal of smart city mission. This article proposes a weighted criteria model to assess the city selection eligibility. The factors are identified from the literature studies. Total interpretive structure modeling is used to analyze the complex interrelationships among the factors and to develop a selection hierarchy. The fuzzy MICMAC process is used to classify the factors based on driving power and dependence. The stabilized driving power is applied to calculate the corresponding weights for each factor. In study findings, the most driving, linkage and dependent factors are identified for analyzing city selection eligibility. The policy-makers, government officials, and decisions-makers would get benefitted from the study outcomes to select top "N" number of cities for Smart Cities Mission.